Social Panorama of Latin America 2015 - Economic Commission for Latin America; the Caribbean (United Nations, 2017)
The 2015 edition of Social Panorama of Latin America analyses poverty trends, as measured by ECLAC. It also examines changes in income distribution and in other aspects of inequality. With a view to contributing to the development of public policies to overcome poverty and socioeconomic inequality, this edition examines the latest trends in social spending and the challenges posed by demographic change, and provides in-depth analysis of persistent gaps in the labour market, of the challenges facing policies and programmes that foster inclusion in the labour market and production, and of social development institutions in Latin America.